A profile of expressive inflectional morphology in early school-age children with developmental language disorder. (4th May 2022) - Calder, Samuel D; Claessen, Mary; Leitão, Suze; Ebbels, Susan
ABSTRACT: Previous research has established that children with developmental language disorder (DLD) have difficulties producing inflectional morphology, in particular, finiteness marking. However, other categories of inflectional morphology, such as possessive 's nominal inflection remain relatively unexplored. Analyses of the characteristics for marking inflection, such as allomorphic categories, may increase our understanding of patterns within disordered grammar to inform the design of interventions and target selection. Data from n = 30 early school-aged children ( M = 75 months, SD  = 3.38, range = 69–81 months) with DLD were analysed to develop a profile of inflectional morphology skills. Morphological categories included expressive regular past tense, third person singular, and possessive 's. Skills were profiled using an elicitation task. The relationships between expressive morphosyntax, and phonological short-term memory and working memory were also explored. Children demonstrated low accuracy in performance across all inflectional categories, including possessive 's . There were no significant differences between productions of different morphemes, but syllabic allomorphs ([əd]; [əz]) were produced with significantly lower accuracy than segmental allomorphs ([d], [t]; [z], [s]) across all morphological categories. All correlations between expressive morphosyntax and measures of memory were non-significant. Children with DLD show broad deficits in the ability to mark for inflection, including possessive 's ; this has implications for theories explaining DLD. Findings may contribute to the design of urgently needed interventions for this clinical population.